Differential management of mild-to-severe psoriasis with biologic drugs: An Italian Delphi consensus expert panel. (April 2015) - Girolomoni, Giampiero; Altomare, Gianfranco; Ayala, Fabio; Berardesca, Enzo; Calzavara Pinton, Piergiacomo; Chimenti, Sergio; Martini, Patrizia; Peserico, Andrea; Puglisi Guerra, Antonio; Antonio Vena, Gino; on behalf on the Delphi working group
Abstract Background: In the management of moderate-to-severe psoriasis, increasingly complex clinical scenarios necessitate practical tools for appropriate biologic therapy selection in individual patients. An Italian Delphi consensus panel provided guidance on biologic use in selected clinical scenarios. Methods: Ten experts defined statements under consideration, which were distributed as an online survey to a dermatologist panel. Plenary discussions of contentious statements were held to achieve consensus. Results: The survey was sent to 30 clinicians. After plenary discussions, consensus was reached on all 20 statements on the following topics: special populations; infections; comorbidities; immunogenicity; extra-cutaneous involvement; pregnancy; and adherence. Three statements required further discussion in order to gain consensus: use of subcutaneous biologics in mild liver impairment (final 94% agreement), use of any biologic in discoid lupus erythematosus (final 100% disagreement), and use of etanercept in patients with history of hypersensitivity reactions to drugs and/or food (final 75% disagreement). Conclusions: This Delphi expert consensus on the use of biologics in psoriasis provides practical recommendations for dermatologists to use when choosing an appropriate biologic in challenging but common clinical scenarios. More data are required to clarify clinical differences of biologic drugs used to treat psoriasis.